Trainee accountants' perceptions of the usefulness of the business ethics curriculum: A case of SAICA in South Africa - Maseko, K.N.; Masinire, A. (South African Journal of Higher Education, 2020)
outThe main research objective of this study was to determine whether Chartered Accountancy (CA) trainees consider business ethics education they received to be useful, and to investigate if it was given the necessary attention at SAICA-accredited universities. The data obtained from CA trainees using a survey was analysed using four theoretical constructs, namely: a) Adequacy of coverage of ethics education, b) Importance of ethics, c) Impact of ethics education on ethical awareness and, d) Effectiveness of ethics education. Kolmogorov-Smirnov and Shapiro-Wilk tests of normality were applied to the theoretical constructs to determine if the data was normally distributed. The Mann-Whitney U test was used to determine if there were significant differences when opinions were categorized according to gender, study mode (part-time or full-time) and highest academic qualification. The Cronbach alpha coefficient was computed to test the reliability of participants’ responses to the survey. The study has found strong agreement among CA trainees that business ethics education is receiving adequate attention at SAICA-accredited universities and is useful in both their professional and personal lives.